Non-contiguous finished genome sequence and description of Bartonella senegalensis sp. nov. Issue 2 (March 2013) - Mediannikov, Oleg; Karkouri, Khalid; Diatta, Georges; Robert, Catherine; Fournier, Pierre-Edouard; Raoult, Didier
Abstract Bartonella senegalensis sp. nov. strain OS02T is the type strain ofB. senegalensis sp. nov., a new species within the genusBartonella . This strain, whose genome is described here, was isolated in Senegal from the soft tickOrnithodoros sonrai, the vector of relapsing fever.B. senegalensis is an aerobic, rod-shaped, Gram-negative bacterium. Here we describe the features of this organism, together with the complete genome sequence and its annotation. The 1, 966, 996 bp-long genome contains 1, 710 protein-coding and 46 RNA genes, including 6 rRNA genes.